Methods of left ventricle shape analysis in assessment and prediction of treatment effect in cardiac dyssynchrony - R. O. Rokeakh; T. V. Chumarnaya; O. E. Solovyova (Российский кардиологический журнал, 2025)
The review discusses the importance of left ventricular shape analysis for diagnosis, severity assessment and prediction of treatment effectiveness in cardiac dyssynchrony. Various methods for assessing the left ventricle shape are consistently considered, starting from the sphericity index common in clinical practice, moving on to more complex and/or rare indices, then to the author's indices of left ventricular functional geometry, as well as to the methods of geometric morphometrics. The results obtained using left ventricular shape analysis in diagnostics and treatment planning are presented.